Penatalaksanaan Anemia Defisiensi Besi Pada Laki - laki Usia 46 Tahun Melalui Pendekatan Kedokteran Keluarga - Tasya Putri Atma Utami Raka; Reni Zuraida (Medula, 2020)
Anemia is one of the health problems in the whole world, especially in developing countries where an estimated 30% of the world's population suffer from anemia. The application of Evidence Base Medicine based services on adult male patients by identifying risk factors and clinical problems and management of patients based on the framework of problem solving and the patient centered approach and family approach. Assessment is based on a holistic diagnosis from the beginning, process, and end of study in a qualitative and quantitative manner. Men aged 46 years, who had been diagnosed with Iron deficiency Anemia had a fear that their complaints would get worse and not improve because after a laboratory examination of Hb patients was 9.8 gr / dl. Limited knowledge about the patient's health conditions in the form of factors that cause anemia, complications from anemia, prevention of anemia, foods that need to be avoided as well as lack of motivation and family encouragement to bring control patients to the nearest health care facility.After a family physician approach is made to anemic patients, there is a change in knowledge about anemia.